2021
DOI: 10.1080/00224545.2021.1917498
|View full text |Cite
|
Sign up to set email alerts
|

Internal and external motivation to respond without prejudice: a person-centered approach

Abstract: With a person-centered approach, the constellations of internal motivation and external motivation to respond without prejudice within individuals are examined, and how these relate to directly and indirectly reported levels of prejudice. Using latent profile analysis, we identified four subgroups of motivated individuals among large national samples of majority members in Germany (N = 1745) and in the Netherlands (N = 1645). With one exception, these subgroups differed in the proportion of prejudiced individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…For example, it might indicate a tendency to respond in a socially desirable way (Nadler et al, 2015). The provision of complete anonymity in online surveys tends to minimize social desirability pressures on self-report measures (Lautenschlager & Flaherty, 1990;Stark et al, 2019), as was found in a survey-embedded experiment in Germany and the Netherlands (Bamberg & Verkuyten, 2021). However, complete anonymity might decrease participants' motivation to respond carefully and thoughtfully (Lelkes et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it might indicate a tendency to respond in a socially desirable way (Nadler et al, 2015). The provision of complete anonymity in online surveys tends to minimize social desirability pressures on self-report measures (Lautenschlager & Flaherty, 1990;Stark et al, 2019), as was found in a survey-embedded experiment in Germany and the Netherlands (Bamberg & Verkuyten, 2021). However, complete anonymity might decrease participants' motivation to respond carefully and thoughtfully (Lelkes et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, theoretically, one potential avenue for future work is to examine whether conservatives might demonstrate a "conservative P-I gap" under conditions of salient personal stake, such that they would show a gap between endorsed conservative principles and their respective behavior under conditions in which behavioral alignment with the principle would have negative personal implications. Consistent with a "conditional approach" to the study of inequality, although the motivations (Bamberg & Verkuyten, 2021), conditions (e.g., target) and manifestations of the P-I gap may differ between the two groups, the outcome (behavior that exacerbates inequality) is likely to be the same. The focus on privileged liberals in the present work, per se, is because one would hope encouraging behavior to achieve equality will be easier to achieve among those that already support (at least in principle) the notion of equality, compared to those that do not.…”
Section: Discussionmentioning
confidence: 99%
“…Person‐centered approaches identify distinct unobserved subgroups of individuals who respond differently to two or more indicator variables. For example, previous research has identified subgroups of individuals that qualitatively differ in the particular ways in which they combine or organize right‐wing authoritarianism and social dominance orientation (Osborne & Sibley, 2017), in their constellation of internal motivation and external motivation to respond without prejudice (Bamberg & Verkuyten, 2021), in the evaluation of a range of Muslim minority practices (Dangubić et al, 2020), and in tolerance of different groups and behaviors (McCutcheon, 1985). Importantly, person‐centered research does not assume linear relations between the perceptions and attitudes used to rank‐order individuals for testing theoretical process models (i.e., variable‐centered approaches), but focuses on more complex and qualitatively distinct constellations within types of people.…”
Section: Introductionmentioning
confidence: 99%